METRIC SPACE OF AIRCRAFT SITUATIONS OF AIRCRAFT - Харченко, В. П.; Корчунов, Д. О. (Proceedings of National Aviation University (archive), 2021)
The principles of constructing metrics as a measure that characterizes the situation of the air situation and its relationship with the probabilities of these situations are considered.